Uncovering a Cryptic Site of Malaria Pathogenesis: Models to Study Interactions Between Plasmodium and the Bone Marrow - Feldman, Tamar P.; Egan, Elizabeth S. (Frontiers in Cellular and Infection Microbiology, 2022)
The bone marrow is a critical site of host-pathogen interactions in malaria infection. The discovery of Plasmodium asexual and transmission stages in the bone marrow has renewed interest in the tissue as a niche for cellular development of both host and parasite. Despite its importance, bone marrow in malaria infection remains largely unexplored due to the challenge of modeling the complex hematopoietic environment in vitro. Advancements in modeling human erythropoiesis ex-vivo from primary human hematopoietic stem and progenitor cells provide a foothold to study the host-parasite interactions occurring in this understudied site of malaria pathogenesis. This review focuses on current in vitro methods to recapitulate and assess bone marrow erythropoiesis and their potential applications in the malaria field. We summarize recent studies that leveraged ex-vivo erythropoiesis to shed light on gametocyte development in nucleated erythroid stem cells and begin to characterize host cell responses to Plasmodium infection in the hematopoietic niche. Such models hold potential to elucidate mechanisms of disordered erythropoiesis, an underlying contributor to malaria anemia, as well as understand the biological determinants of parasite sexual conversion. This review compares the advantages and limitations of the ex-vivo erythropoiesis approach with those of in vivo human and animal studies of the hematopoietic niche in malaria infection. We highlight the need for studies that apply single cell analyses to this complex system and incorporate physical and cellular components of the bone marrow that may influence erythropoiesis and parasite development.